CO2 capture technology based on gas hydrate method: a review - Pei, Jialing; Chen, Jinger; Wang, Jingxue; Li, Zhi; Li, Nan; Kan, Jingyu (Frontiers in Chemistry, 2024)
At present, the problem of global warming is becoming increasingly serious, and one of the main culprits is the increasing amount of carbon dioxide emissions. Although the traditional carbon capture technologies can reduce the concentration of CO2 in the atmosphere, it has a series of problems such as high energy consumption, high cost, low efficiency or unfriendly environment. Hydrate-based carbon dioxide separation are considered to be a technology with great application and development prospects. Compared with the traditional method of carbon dioxide separation, the hydrate method has the advantages of simple process, low energy consumption and environmental friendliness. This review introduces the advantages of hydrate method compared with traditional carbon capture technologies, expounds the theory of carbon dioxide capture by hydrate, and the strengthening and improvement techniques of hydrate method, including thermodynamic promoter, kinetic promoter and mechanical reinforcement, and introduces the practical application of hydrate method in various fields.